Private security and the law - Nemeth, Charles P. (Elsevier Butterworth Heinemann, 2005)
PRIVATE SECURITY AND THE LAW is a textbook analysis of significant practices in the security industry that relate to law, regulation, licensure and constitutional dilemmas according to case and statutory authority. It is a treatise on the state of the law that governs the security industry and its operatives. The text delivers up to date information on the legal requirements witnessed by most security firms. In addition, it dwells heavily on the liability problems common to security operations, including negligence and tortious liability, civil actions commonly litigated, and strategies to avoid troublesome causes of action that effect business efficiency. From another angle, the work intensely examines the constitutional and due process dimensions of private security work and affords the reader a look at how case law applies certain remedies to wronged parties. Recent cases, and the trends sure to follow, are highlighted throughout the project. Finally, the text is filled with checklists, data and other useful information that aids the security practitioner in applying theory to practice.